Efforts to Improve Students's Speaking Abilities by Applying The Word Guessing Learning Model Indonesian Language Subjects in UPT SPF State Elementary School 10422 SEI Glugur Deli Serdang - Netti Hasugian, Sinta; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence, 2026)
This study aims to determine the effect of the Word Guessing learning model in improving the speaking skills of fourth grade students of UPT SPF SD Negeri 104222 Sei Glugur, Deli Serdang Regency. This study uses a quasi-experimental method (Quasi Experimental) with a pretest-posttest control group design. The population of the study was three classes with a total of 74 students, while the sample consisted of two classes selected by purposive sampling, namely classes IVA and IVB, each consisting of 25 students. Data collection techniques were carried out through observation, speaking skills tests, and documentation. Data analysis used descriptive and inferential statistics. The results showed that in the experimental group, the average pre-test score was 66, with 40% of students in the Poor category. After the application of the Guess the Word model, the average post-test increased to 85, with 44% of students in the Very Good category. Meanwhile, the control group using the conventional model obtained an average pre-test of 58, with 32% of students in the Poor category, and the average post-test increased to 75, with 40% of students in the Good category. Inferential analysis showed that the t-value of 9.26 was greater than t-table (2.06) at a significance level of 0.05, so the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Thus, the Guess the Word model has a significant effect on students' speaking skills. The implication of this study is that the application of the Guess the Word model can improve students' speaking fluency in learning Indonesian more effectively